2018
DOI: 10.1016/j.jelechem.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of activated carbon obtained from peach stone as an electrochemical sensor for detecting caffeine

Abstract: Simple, economical and highly sensitive electrodes for the detection of caffeine by using activated carbon from peach stones have been developed. The activated carbons were synthesized by chemical activation using ZnCl 2 and ZnCl 2 :FeCl 3 (1:1) as chemical agents, producing carbons with different textural properties and morphologies, which led to differences in the electroactive area of the materials that affected the electrochemical response to caffeine. The electrodes presented a linear response in the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Through a comparison of the data obtained at the GrRAC and GrRGC electrodes with the existing literature, Table 2 shows the significant examples published so far, concerning the different electrodes used for the determination of caffeine. For example, the CA-ZnFe modified glassy carbon electrode exhibits a LOD higher than the values shown by the GrRAC and GrRGC caffeine sensors reported in this work [ 6 ]. Conversely, the EPPGE sensor exhibits a lower LOD, approximately 0.008 µM, compared to GrRAC and GrRGC [ 11 ].…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Through a comparison of the data obtained at the GrRAC and GrRGC electrodes with the existing literature, Table 2 shows the significant examples published so far, concerning the different electrodes used for the determination of caffeine. For example, the CA-ZnFe modified glassy carbon electrode exhibits a LOD higher than the values shown by the GrRAC and GrRGC caffeine sensors reported in this work [ 6 ]. Conversely, the EPPGE sensor exhibits a lower LOD, approximately 0.008 µM, compared to GrRAC and GrRGC [ 11 ].…”
Section: Resultsmentioning
confidence: 55%
“…Nowadays, the development of electrochemical sensing tools for various applications is receiving great attention [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Due to their inherent specificity, rapid measurement procedures, high accuracy, high sensitivity and simplicity of preparation, these measuring devices allow monitoring of different species in a satisfactory way.…”
Section: Introductionmentioning
confidence: 99%
“…The use of MnCl 2 yielded the activated carbon with the highest porous surface area and pore volume, although the activated carbon prepared using FeCl 3 showed the highest Cr(VI) adsorption capacities. Arroyo-Gómez et al [80] synthesized activated carbons from peach stones by chemical activation with only ZnCl 2 and a mixture of ZnCl 2 and FeCl 3 (1:1). The study affirmed that the activated carbon obtained with the ZnCl 2 -FeCl 3 mixture showed the highest sensitivity in caffeine detection, probably due to the lower roughness and the presence of mesopores resulting in a better mobility of the caffeine molecules.…”
Section: Mixtures Of Activating Agentsmentioning
confidence: 99%
“…Activated carbon materials play important roles as electrode materials and have been used to manufacture EDLCs, including commercially available commercial devices. This is because of the excellent electrochemical performance, resulting from their large surface area, tunable pore sizes, chemical resistance, non-corrosion properties, and good electrical conductivities [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, the precursors of most carbon materials are usually derived from fossil fuels, which strongly detracts from the environmental benefits of their use.…”
Section: Introductionmentioning
confidence: 99%